Deterministic approach to design passive anomalous-diffraction metasurfaces with nearly 100% efficiency - Fang Zhening; Li Haipeng; Chen Yan; Sun Shulin; Xiao Shiyi; He Qiong; Zhou Lei (Nanophotonics)
Designing perfect anomalous reflectors is crucial for achieving many metasurface-based applications, but available design approaches for the cases of extremely large bending angles either require unrealistic gain–loss materials or rely on brute-force optimizations lacking physical guidance. Here, we propose a deterministic approach to design passive metasurfaces that can reflect impinging light to arbitrary nonspecular directions with almost 100% efficiencies. With both incident and out-going far-field waves given, we can retrieve the surface-impedance profile of the target metadevice by matching boundary conditions with all allowed near-field modes added self-consistently and then construct the metadevices deterministically based on passive meta-atoms exhibiting local responses. We design/fabricate two proof-of-concept microwave metadevices and experimentally demonstrate that the first one achieves anomalous reflection to a 70° angle with efficiency ∼98%, and the second one can generate multiple reflected beams with desired bending angles and power allocations. Our findings pave the way for realizing high-efficiency wave-control metadevices with desired functionalities.